Performance Evaluation of Vertical Bell Labs Layered Space Time (Vblast) Algorithms For Mimo System - Jamel, Thamer M.; Hadi, Nooreldeen R. (Nahrain University College of Engineering Journal, 2010)
In this paper a possible way of MIMO technique is used to exploit the multipath scattering properly, it is the Spatial Multiplexing, where the parallel streams of data are mixed up in the air but can be recovered at the receiver by using different Vertical Bell Labs Layered Space- Time (VBLAST algorithms like, Zero Forcing (ZF), Minimum Mean Square Error (MMSE), and QR-decomposition decoding methods. This paper focused in performance evaluation between these different algorithms in terms of Bit Error Rate (BER) performance using different modulation schemes (4PSK, 8PSK, 16PSK, and 16QAM), and different numbers of antennas. The results derived have shown that 4PSK has the best performance and 16PSK has the worst for all different types of receiver algorithms, with 16QAM constellation performance better than 16PSK, although they use the same bit rate. The BER performance degrades when the constellation size increases. Also the VBLAST receivers with VBLASTMMSE perform better than VBLAST-ZF and VBLAST-QR receiver in terms of BER when 2X2 antennas are used. Also, it is noted that with increasing modulation constellation the curves of BER are shifted to right due to the higher data rate that is transmitted. MMSE loses the advantage over ZF that is observed for lower constellations, and VBLAST-QR performs better than lower constellations. Finally it is noticed that the BER performance degrades with increasing the number of antennas.